Electromechanical window negativity in genotyped long-QT syndrome patients: relation to arrhythmia risk - ter Bekke, Rachel M.A.; Haugaa, Kristina H.; van den Wijngaard, Arthur; Bos, J. Martijn; Ackerman, Michael J.; Edvardsen, Thor; Volders, Paul G.A. (European heart journal, 2015)
Prolonged and dispersed left-ventricular (LV) contraction is present in patients with long-QT syndrome (LQTS). Electrical and mechanical abnormalities appear most pronounced in symptomatic individuals. We focus on the 'electromechanical window' (EMW; duration of LV-mechanical systole minus QT interval) in patients with genotyped LQTS. Profound EMW negativity heralds torsades de pointes in animal models of drug-induced LQTS. We included 244 LQTS patients from three centres, of whom 97 had experienced arrhythmic events. Seventy-six matched healthy individuals served as controls. QT interval was subtracted from the duration of Q-onset to aortic-valve closure (QAoC) midline assessed non-invasively by continuous-wave echocardiography, measured in the same beat. Electromechanical window was positive in controls but negative in LQTS patients (22 ± 19 vs. -43 ± 46 ms; P < 0.0001), being even more negative in symptomatic than event-free patients (-67 ± 42 vs. -27 ± 41 ms; P < 0.0001). QT, QTc, and QAoC were longer in LQTS subjects (451 ± 57, 465 ± 50, and 408 ± 37 ms, P < 0.0001). Electromechanical window was a better discriminator of patients with previous arrhythmic events than resting QTc (AUC 0.77 (95% CI, 0.71-0.83) and 0.71 (95% CI, 0.65-0.78); P = 0.03). In multivariate analysis, EMW predicted arrhythmic events independently of QTc (odds ratio 1.25; 95% CI, 1.11-1.40; P = 0.001). Adding EMW to QTc for risk assessment led to a net reclassification improvement of 13.3% (P = 0.03). No EMW differences were found between the three major LQTS genotypes. Patients with genotype-positive LQTS express EMW negativity, which is most pronounced in patients with documented arrhythmic events.